Comparative Pitching Biomechanics Among Adolescent Baseball Athletes: Are There Fundamental Differences Between Pitchers and Non-pitchers? - Garrett Bullock; Tessa C Hulburt; Gary Collins; Brian R Waterman; Kristen F Nicholson (North American Sports Medicine Institute, 2021)
# Background Approximately 25% of youth baseball players pitch, with most young athletes predominately playing multiple positions. While some youth baseball players may primarily pitch, other players may only pitch on occasion, potentially creating a pitching skill level discrepancy. Understanding potential kinematic and kinetic differences between pitching and non-pitching baseball players can inform injury risk reduction strategies for amateur athletes. # Purpose/Hypothesis To analyze differences in pitching biomechanics for fastballs, breaking balls, and change-ups in adolescent youth baseball players that identify as pitchers and non-pitchers. # Study Design Retrospective cross-sectional study # Methods Baseball players were designated as pitchers or non-pitchers, who then threw fastballs (FB), breaking balls (BB), and change-ups (CH) during a biomechanical assessment. T-tests, Mann-Whitney U tests, and ANOVAs with Bonferroni correction, and effect sizes (ES) were performed. # Results Sixty baseball players (pitchers = 40; non-pitchers = 20; Age: 15.0 (1.1); Left-handed: 15%; Height 1.77 (0.09) m; Weight: 70.0 (12.5) kg) threw 495 pitches (FB: 177, BB: 155, CH: 163) for analysis. Pitchers threw 2 m/s faster and produced greater trunk rotation velocity (ES: 0.71 (95% CI: 0.39, 1.30, p\<0.0001) than non-pitchers. Furthermore, pitchers demonstrated greater ground reaction force for FB compared to CH (ES: 0.48 (95% CI: 0.01, 0.94), p\<0.0001). No other biomechanical differences were observed between pitchers and non-pitchers or between pitch types. # Conclusion Despite throwing at greater velocity for all pitch types, baseball players that identify primarily as pitchers had overall similar kinematics and kinetics in comparison to baseball players that primarily identify as non-pitchers. Self-identified pitching baseball athletes have improved force transfer strategies for ball propulsion, utilizing different force production and attenuation strategies across different pitch types when compared to non-pitchers. Coaches should consider that novice pitchers may potentially have dissimilar trunk and ground reaction strategies in comparison to primary pitchers when designing appropriate pitch loading and recovery strategies. # Level of Evidence 3